Hostility in political debates online and offline: Who are the offenders - and who are the victims? - Petersen, Michael Bang; Bor, Alexander (Politica, 2022)
Hostile behavior on social media in connection with, for example, political discussions, is considered a growing societal problem. In this article, we ask: Who are the perpetrators of political hostility on the Internet – and who are the victims? And are the perpetrators and victims of hostility on the Internet different from the victims outside the Internet? The analyses show that the people who act in hostile ways and report being targeted by hostility in connection with political discussions are largely the same both online and offline. Aggressive behavior is generally more prevalent among young men, and the analyses show that it is also primarily young men who behave in hostile ways both online and offline. Consistent with knowledge of aggression in general, hostility is also directed primarily at other young men. Thus, Internet hostility does not appear to be a particular form of hatred or aggression. Those who are aggressive offline are also aggressive online, and they seek out the same victims both places. Keywords: social media, political debates, hostility, personality